Pulmonary valve infective endocarditis: A case series - SatyavanSharma; Gunjan Arvindbhai Malavia (Wolters Kluwer Medknow Publications, 2021)
Background and Objectives : Infective endocarditis (IE) involving the native pulmonary valve (PV) is extremely rare, with no data in Indian literature. The objective of this communication is to describe the clinical and diagnostic characteristics, underlying risk factors, microbiological features, and management of PVIE. Methods : This is a retrospective analysis of 8 cases of PVIE managed in a tertiary care center from 1992 to 2020. Results : PVIE was observed in 8 patients with underlying congenital cardiac malformation (Group A, 6 Patients) and in patients with central venous catheter (Group B, 2 patients). All the patients had prolonged febrile illness accompanied by right heart failure 4 (50%), septic pulmonary emboli 2 (25%), and pulmonary regurgitation 3 (37.5%). Trans-thoracic echocardiography demonstrated the vegetations, whereas computed tomography of chest diagnosed pulmonary emboli in 2 (25%), and pulmonary artery aneurysm in 1 (12.5%) patient. The early mortality was extremely high (5, 62.5%). Delayed diagnosis, fulminant septicemia, and multi-organ failure resulted in unfavorable outcomes. Conclusions : IE of the native PV is a rare and potentially lethal illness. Diagnosis should be considered in any febrile patient with an underlying congenital defect, central venous line, bacteremia, and comorbidities. Multi-modality imaging should be utilized to enhance the diagnostic yield and detect complications promptly.